Space debris peril : pathways to opportunities - Madi, Matteo; Sokolova, Olga (Boca Raton : CRC Press, 2021)
"This book provides up-to-date knowledge of space debris and valuable insights on how to grapple with this issue from legal, technical, economical and societal aspects. I would strongly recommend that everyone who is working on space development and utilizations and even non-specialists once read this book and think over how human being should be faced with this issue." -Prof. Shinichi Nakasuka, University of Tokyo, Japan Space Debris Peril: Pathways to Opportunities takes readers through the wide spectrum of problems created by space debris - including technical, political, legal and socio-economical aspects - and suggests ways to mitigate its negative consequences and create new opportunities. With chapter contributions from authors at world-renowned universities, private or public entities, and research institutes active in the field of space debris mitigation, space policy and law, risk and resilience, liability and insurance, this book provides a comprehensive introduction to the subject helping the reader to grasp the whole picture of the current space debris remediation challenges. This book will be of interest to the scientific communities, policy makers, business developers, (re)insurers and international standards developers for space operations and orbital debris mitigation. Also, it should appeal to a broader audience among non-specialists in various sectors and the general public. Key features: Brings together interdisciplinary perspectives on the topic in one, cohesive book Chapter contributions from specialists in this interdisciplinary field from around the globe Up-to-date information with the latest developments
OCLC-licensed vendor bibliographic record.
Keywords: Space debris; SCIENCE / Astrophysics & Space Science; LAW / Environmental